A biochar-based organic pollutant adsorption material
By grafting nano-TiO2 coated nano-SiO2 and Fe3O4-laden biochar on porous zeolites, an efficient organic pollutant adsorption material is formed, which solves the insufficient adsorption capacity, high cost and insufficient environmental protection of polycyclic aromatic hydrocarbon organic pollutants. The problem of this has achieved efficient and environmentally friendly pollutant removal effect.
Patent Information
- Application Number
- CN202411233667.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-04
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-09-04
AI Technical Summary
The prior art has problems of insufficient adsorption capacity, high cost and insufficient environmental protection in removing polycyclic aromatic hydrocarbon organic pollutants.
Biochar-based organic pollutant adsorbent material is formed by grafting the nano-SiO2 coated nano-TiO2 onto the modified porous zeolite and topologically reacting with the Fe3O4-loaded biochar.
It improves the adsorption performance and photooxidation and degradation efficiency of polycyclic aromatic hydrocarbon organic pollutants, reduces the adsorption removal cost, and enhances the environmental protection and stability of the material.
Smart Images

Figure BDA0005027067280000111 
Figure BDA0005027067280000121
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of organic pollutant adsorption, and in particular to an organic pollutant adsorption material based on biochar. Background Art
[0002] Common organic pollutants, polycyclic aromatic hydrocarbons, are hydrocarbon organic chemical pollutants containing two or more benzene rings and have the "three hazard" effects of carcinogenicity, teratogenicity, and mutagenicity. They are widely present in the atmosphere, water, soil, and animals and plants, and are persistent organic pollutants that exist in the natural environment for a long time. The extraction and use of fossil fuels has led to a continuous increase in polycyclic aromatic hydrocarbon organic pollutants in the soil, affecting the growth of crops and threatening human health. Therefore, how to remove polycyclic aromatic hydrocarbons has always been one of the important research directions in the field of pollutant treatment.
[0003] Biochar refers to a carbon-rich material with a high degree of aromatization and a large specific surface area produced by biomass materials such as sludge, animal manure and plant residues under anaerobic or anoxic conditions and a certain pyrolysis temperature. Because it contains abundant oxygen-containing functional groups and a large porosity, it has a good adsorption and stabilization effect on pollutants present in the ecological environment (water, soil or sediment). However, in the field of environmental protection, especially in the application of water pollutant removal, these carbon materials have the disadvantages of light weight, fine particles and difficulty in separation, which limits their practical application. In addition, biochar may involve high-temperature treatment during the production process, which has a greater impact on the environment, so its environmental friendliness is insufficient.
[0004] Zeolite is widely used in various fields as an adsorbent, filter medium, ion exchanger, chemical carrier, molecular sieve and catalyst. In particular, due to its large adsorption capacity, selective adsorption and high-efficiency adsorption characteristics, it is used as an environmentally friendly and coordinated material in the field of environmental protection. However, the porous zeolite is not hydrophobic and lipophilic, which makes its adsorption capacity for non-polar organic matter such as polycyclic aromatic hydrocarbons poor. In addition, after porous zeolite adsorbs organic pollutants such as polycyclic aromatic hydrocarbons, the adsorbed organic matter is generally removed by backwashing and chemical washing, which is a relatively costly method.
[0005] Nano-TiO 2 It is the most widely used photocatalytic material. Under photocatalytic action, nano-TiO 2 The surface can form electron pairs and holes as well as stable electron transport interface orbitals, providing a large number of chemical reaction sites for photocatalytic reactions, which can degrade organic pollutants into H 2 O and CO 2 Non-toxic substances such as nano-TiO 2 Due to insufficient absorption of visible light, the energy of visible light cannot be effectively utilized for photocatalytic reactions.
[0006] Therefore, a suitable modification method is developed to obtain a product that is not only environmentally friendly and has high adsorption capacity for polycyclic aromatic hydrocarbons, but can also oxidize them into non-toxic H 2 O and CO 2 The biochar-based porous zeolite and nano-titanium dioxide composite adsorption materials have practical significance. Summary of the invention
[0007] In order to solve the above technical problems, the present invention provides an organic pollutant adsorption material based on biochar.
[0008] The purpose of the present invention can be achieved through the following technical solutions:
[0009] A biochar-based organic pollutant adsorption material is prepared by the following steps:
[0010] Step S1: placing N,N-dimethyl-7-aminoheptanoic acid and ethanol in a flask, stirring, then adding pentadecane chloride, heating to 30-40° C., stirring at constant temperature for 10-12 hours, revolving and recrystallizing with acetone, filtering, and obtaining a quaternary ammonium salt product; adding the quaternary ammonium salt product into distilled water, stirring for 10 minutes, adding porous zeolite, and then oscillating in a water bath at a temperature of 60-70° C. and a rotation speed of 200 r / min for 48-51 hours, washing with water and drying, and obtaining a modified zeolite;
[0011] Further, the dosage ratio of N,N-dimethyl-7-aminoheptanoic acid, ethanol, and chloropentadecane is 0.1 mol: 85-95 mL: 0.1 mol, and the volume fraction of ethanol is 95%; the dosage ratio of the quaternary ammonium salt product, distilled water, and porous zeolite is 0.05-0.1 mol: 1000 mL: 300-400 g, and the size of the porous zeolite is 200 mesh;
[0012] During the reaction of step S1, the tertiary amine group of N,N-dimethyl-7-aminoheptanoic acid reacts with the chlorine atom of chloropentadecane to generate a quaternary ammonium salt product containing a carboxyl group and a long alkane chain; the quaternary ammonium cation of the quaternary ammonium salt product modifies the porous zeolite to obtain a modified zeolite containing a carboxyl group and a long alkane chain;
[0013] Step S2: Add nano titanium dioxide into deionized water, ultrasonically disperse for 30-40 minutes, then add sodium hexametaphosphate, adjust the pH to 8-9, heat to 80°C under vigorous stirring, adjust the pH to 10.0, slowly add hydrated silicon dioxide, continue stirring for 1 hour, slowly adjust the pH to 7.0, continue stirring for 30 minutes, filter, wash with water, and dry to obtain surface-coated nano SiO 2 Nano-TiO 2 ; Then the surface is coated with nano-SiO 2 Nano-TiO 2Add to anhydrous ethanol, ultrasonically disperse for 15 minutes, add 5-hexenyltrimethoxysilane and sulfuric acid solution, stir for 30-40 minutes, and obtain a coated product with double bonds on the surface;
[0014] Furthermore, the dosage ratio of nano titanium dioxide, deionized water, sodium hexametaphosphate, and hydrated silicon dioxide is 5-10 g: 50-60 mL: 3-6 g: 0.05-0.1 g; the surface is coated with nano SiO 2 Nano-TiO 2 , anhydrous ethanol, 5-hexenyltrimethoxysilane and sulfuric acid solution in a ratio of 6-8 g: 70-80 mL: 42-45 g: 8-10 mL, and the concentration of the sulfuric acid solution is 0.1 mol / L;
[0015] In the reaction process of step S2, nano-silicon dioxide is physically coated on the surface of nano-titanium dioxide by a sol-gel method, and then 5-hexenyltrimethoxysilane is hydrolyzed and reacted with the silanol groups on the surface of the nano-silicon dioxide to obtain a coated product with double bonds on the surface;
[0016] Step S3: adding the coated product containing double bonds on the surface to dichloromethane, stirring, and then adding 3-chloroperoxybenzoic acid, stirring and reacting at room temperature for 4-5 hours to obtain an epoxy product; in a nitrogen atmosphere, adding the modified zeolite and toluene to a flask, heating to 45° C., adding pyridine, stirring, adding the epoxy product to the flask, stirring and reacting for 8-10 hours, and then heating to 110-120° C., stirring for 1-2 hours to obtain a hydroxyl product;
[0017] Further, the amount ratio of the coated product containing double bonds on the surface, dichloromethane and 3-chloroperoxybenzoic acid is 13-15 g: 100-110 mL: 36-40 g; the amount ratio of the modified zeolite, toluene, pyridine and epoxy product is 32-35 g: 140-150 mL: 5-6 mol: 21-23 g;
[0018] In the reaction process of step S3, the carbon-carbon double bonds in the coated product containing double bonds on the surface are oxidized to epoxy groups to obtain epoxy products; the carboxyl groups in the modified zeolite react with the epoxy groups of the epoxy products to generate hydroxyl products, thereby coating the surface of the nano-SiO 2 Nano-TiO 2 Graft-supported in porous zeolite;
[0019] Step S4: Add biochar and oleylamine to a three-necked flask and ultrasonically disperse for 20 minutes, then add ferric acetylacetonate, introduce nitrogen for 10 minutes, heat to 200°C with stirring and continue stirring for 30-40 minutes, continue to heat to 280°C and continue stirring for 30-40 minutes, cool to room temperature, wash with n-hexane and anhydrous ethanol for 6 times respectively, and dry to obtain the loaded Fe 3O 4 of biochar;
[0020] Further, the dosage ratio of biochar, oleylamine, and ferric acetylacetonate is 1.0 g: 60 mL: 2.0 g, the biochar is one of rice straw biochar, coconut shell biochar, and sawdust biochar, and the particle size of the biochar is 4-6 nm;
[0021] In step S4, the Fe acetylacetonate is prepared by high-temperature decomposition of an organic precursor. 3 O 4 Nanoparticles are loaded in biochar;
[0022] Step S5: Load Fe 3 O 4 The biochar is added to the mixed acid solution, stirred and reacted at 40-50°C for 3-5h, filtered, washed with deionized water, and vacuum dried at 80°C for 4h to obtain a surface carboxylation biochar product; the surface carboxylation biochar product, hydroxyl product, anhydrous ethanol, and N, N'-dicyclohexyl diimide are added to the reaction bottle under stirring, the temperature is raised to 110-120°C, and the reaction is stirred under constant temperature reflux for 48h, and then centrifuged through isopropanol, and the lower precipitate is vacuum dried at 80°C for 24h to obtain a biochar-based organic pollutant adsorption material;
[0023] Furthermore, Fe 3 O 4 The dosage ratio of biochar and mixed acid solution is 10g:30-35mL, the mixed acid solution is prepared by mixing concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 3:1, and the mass fractions of concentrated sulfuric acid and concentrated nitric acid are both 98%; the dosage ratio of surface carboxylation biochar product, hydroxyl product, anhydrous ethanol, and N,N'-dicyclohexyl diimide is 12-14g:25-30g:200-250mL:30-35g;
[0024] During the reaction of step S5, Fe is loaded 3 O 4 The surface of the biochar was carboxylated after mixed acid treatment, and the surface carboxylated biochar product was then grafted with the hydroxyl product through topological reaction under the action of N, N'-dicyclohexyl diimide, thereby loading Fe 3 O 4 The biochar was grafted and loaded into porous zeolite to generate biochar-based organic pollutant adsorption materials.
[0025] Beneficial effects of the invention: The invention discloses an organic pollutant adsorption material based on biochar, which uses a 200-mesh porous zeolite as a carrier, firstly uses a quaternary ammonium salt containing an alkane long chain and a carboxyl group as a cationic surfactant to modify the porous zeolite, and then nano-SiO 2 Coated nano-TiO2 The surface carboxyl-loaded Fe 3 O 4 The biochar product reacts with the hydroxyl groups generated by the ring-opening product through topological reaction to load Fe 3 O 4 Biochar with porous zeolite and nano-SiO 2 Coated nano-TiO 2 The grafted one has better stability.
[0026] After the porous zeolite is modified by a quaternary ammonium salt cationic surfactant containing a long alkane chain, the long alkane chain enhances the compatibility of the porous zeolite with non-polar polycyclic aromatic hydrocarbon organic pollutants, thereby increasing the adsorption of polycyclic aromatic hydrocarbon organic pollutants by the adsorbent material, and can also reduce the amount of biochar used, making up for the disadvantage of biochar adsorption materials that are not environmentally friendly due to the high temperature preparation process required. Biochar loaded with Fe 3 O 4 Finally, the biochar-based organic pollutant adsorption material is made magnetic and can be collected by magnetic adsorption, thus avoiding the adverse effects of the adsorption material on the environment due to its light weight, small particles and difficulty in separation. 2 Coated nano-TiO 2 Afterwards, due to nano-SiO 2 The high refractive index can increase the scattering of visible light, allowing more photons to be absorbed by nano-TiO 2 absorption, thereby improving the nano-TiO 2 The utilization rate of visible light can improve the nano-TiO 2 The photo-oxidative degradation efficiency of polycyclic aromatic hydrocarbons organic pollutants is improved by porous zeolite and Fe 3 O 4 The polycyclic aromatic hydrocarbons adsorbed by the biochar can be oxidized to non-toxic H 2 O and CO 2 The organic pollutants adsorbed by the porous zeolite need to be removed by backwashing and chemical washing, which reduces the cost of adsorbing and removing polycyclic aromatic hydrocarbon organic pollutants. Therefore, the biochar-based organic pollutant adsorption material of the present invention has excellent adsorption performance for polycyclic aromatic hydrocarbon organic pollutants, is highly environmentally friendly, can reduce adsorption costs, and is worthy of promotion. DETAILED DESCRIPTION
[0027] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0028] Example 1
[0029] A biochar-based organic pollutant adsorption material, the preparation of which comprises the following steps:
[0030] Step S1: placing N,N-dimethyl-7-aminoheptanoic acid and ethanol in a flask, stirring, then adding chloropentadecane, heating to 30°C, stirring at a constant temperature for 10 hours, revolving and recrystallizing with acetone, filtering, and obtaining a quaternary ammonium salt product; adding the quaternary ammonium salt product into distilled water, stirring for 10 minutes, adding porous zeolite, and then oscillating in a water bath at a temperature of 60°C and a speed of 200r / min for 48 hours, washing with water and drying, and obtaining a modified zeolite; the amount ratio of N,N-dimethyl-7-aminoheptanoic acid, ethanol, and chloropentadecane is 0.1mol:85mL:0.1mol, and the volume fraction of ethanol is 95%; the amount ratio of the quaternary ammonium salt product, distilled water, and porous zeolite is 0.05mol:1000mL:300g, and the size of the porous zeolite is 200 mesh;
[0031] Step S2: Add nano titanium dioxide into deionized water, ultrasonically disperse for 30 minutes, then add sodium hexametaphosphate, adjust the pH to 8, heat to 80°C under vigorous stirring, adjust the pH to 10.0, slowly add hydrated silicon dioxide, continue stirring for 1 hour, slowly adjust the pH to 7.0, continue stirring for 30 minutes, filter, wash with water, and dry to obtain surface-coated nano SiO 2 Nano-TiO 2 ; Then the surface is coated with nano-SiO 2 Nano-TiO 2 Add to anhydrous ethanol, ultrasonically disperse for 15 minutes, add 5-hexenyltrimethoxysilane and sulfuric acid solution, stir for 30 minutes, and obtain a coated product with double bonds on the surface; the dosage ratio of nano titanium dioxide, deionized water, sodium hexametaphosphate, and hydrated silicon dioxide is 5g: 50mL: 3g: 0.05g; the surface coated nano SiO 2 Nano-TiO 2 , anhydrous ethanol, 5-hexenyltrimethoxysilane and sulfuric acid solution in a ratio of 6 g:70 mL:42 g:8 mL, and the concentration of the sulfuric acid solution is 0.1 mol / L;
[0032] Step S3: adding the coated product containing double bonds on the surface to dichloromethane, stirring, and then adding 3-chloroperoxybenzoic acid, stirring and reacting at room temperature for 4-5 hours to obtain an epoxy product; in a nitrogen atmosphere, adding the modified zeolite and toluene to a flask, heating to 45°C, adding pyridine, stirring, adding the epoxy product to the flask, stirring and reacting for 8 hours, and then heating to 110°C, stirring for 1 hour, to obtain a hydroxyl product; the amount ratio of the coated product containing double bonds on the surface, dichloromethane and 3-chloroperoxybenzoic acid is 13g:100mL:36g; the amount ratio of the modified zeolite, toluene, pyridine and epoxy product is 32g:140mL:5mol:21g;
[0033] Step S4: Add biochar and oleylamine to a three-necked flask and ultrasonically disperse for 20 minutes, then add ferric acetylacetonate, introduce nitrogen for 10 minutes, heat to 200°C with stirring and continue stirring for 30 minutes, continue to heat to 280°C and continue stirring for 30 minutes, cool to room temperature, wash with n-hexane and anhydrous ethanol for 6 times respectively, and dry to obtain the loaded Fe 3 O 4 The amount ratio of biochar, oleylamine and ferric acetylacetonate is 1.0 g: 60 mL: 2.0 g, the biochar is sawdust biochar, and the particle size of the biochar is 4 nm;
[0034] Step S5: Load Fe 3 O 4 The biochar was added to the mixed acid solution, stirred at 40 ° C for 3 hours, filtered, washed with deionized water, and vacuum dried at 80 ° C for 4 hours to obtain a surface carboxylation biochar product; the surface carboxylation biochar product, hydroxyl product, anhydrous ethanol, and N, N'-dicyclohexyl diimide were added to the reaction bottle under stirring, the temperature was raised to 110 ° C, and the reaction was stirred at constant temperature reflux for 48 hours, and then centrifuged through isopropanol, and the lower precipitate was vacuum dried at 80 ° C for 24 hours to obtain a biochar-based organic pollutant adsorption material; Fe loaded 3 O 4 The dosage ratio of biochar and mixed acid solution is 10g:30mL, the mixed acid solution is prepared by mixing concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 3:1, and the mass fractions of concentrated sulfuric acid and concentrated nitric acid are both 98%; the dosage ratio of surface carboxylation biochar product, hydroxyl product, anhydrous ethanol, and N,N'-dicyclohexyldiimide is 12g:25g:200mL:30g.
[0035] Example 2
[0036] A biochar-based organic pollutant adsorption material, the preparation of which comprises the following steps:
[0037] Step S1: placing N,N-dimethyl-7-aminoheptanoic acid and ethanol in a flask, stirring, and then adding chloropentadecane, heating to 35°C, stirring at a constant temperature for 11 hours, revolving and recrystallizing with acetone, filtering, and obtaining a quaternary ammonium salt product; adding the quaternary ammonium salt product into distilled water, stirring for 10 minutes, adding porous zeolite, and then oscillating in a water bath at a temperature of 65°C and a speed of 200r / min for 50 hours, washing with water and drying, and obtaining a modified zeolite; the amount ratio of N,N-dimethyl-7-aminoheptanoic acid, ethanol, and chloropentadecane is 0.1mol:90mL:0.1mol, and the volume fraction of ethanol is 95%; the amount ratio of the quaternary ammonium salt product, distilled water, and porous zeolite is 0.08mol:1000mL:350g, and the size of the porous zeolite is 200 mesh;
[0038] Step S2: Add nano titanium dioxide into deionized water, ultrasonically disperse for 35 minutes, then add sodium hexametaphosphate, adjust the pH to 8, heat to 80°C under vigorous stirring, adjust the pH to 10.0, slowly add hydrated silicon dioxide, continue stirring for 1 hour, slowly adjust the pH to 7.0, continue stirring for 30 minutes, filter, wash with water, and dry to obtain surface-coated nano SiO 2 Nano-TiO 2 ; Then the surface is coated with nano-SiO 2 Nano-TiO 2 Add to anhydrous ethanol, ultrasonically disperse for 15 minutes, add 5-hexenyltrimethoxysilane and sulfuric acid solution, stir for 35 minutes, and obtain a coated product with double bonds on the surface; the dosage ratio of nano titanium dioxide, deionized water, sodium hexametaphosphate, and hydrated silicon dioxide is 8g: 55mL: 4.5g: 0.08g; the surface coated nano SiO 2 Nano-TiO 2 , anhydrous ethanol, 5-hexenyltrimethoxysilane and sulfuric acid solution in a ratio of 6-8 g: 75 mL: 43 g: 9 mL, and the concentration of the sulfuric acid solution is 0.1 mol / L;
[0039] Step S3: adding the coated product containing double bonds on the surface to dichloromethane, stirring, and then adding 3-chloroperoxybenzoic acid, stirring and reacting at room temperature for 4.5 hours to obtain an epoxy product; in a nitrogen atmosphere, adding the modified zeolite and toluene to a flask, heating to 45°C, adding pyridine, stirring, adding the epoxy product to the flask, stirring and reacting for 9 hours, and then heating to 115°C, stirring for 1.5 hours to obtain a hydroxyl product; the amount ratio of the coated product containing double bonds on the surface, dichloromethane and 3-chloroperoxybenzoic acid is 14g:105mL:38g; the amount ratio of the modified zeolite, toluene, pyridine and epoxy product is 33g:145mL:5.5mol:22g;
[0040] Step S4: Add biochar and oleylamine to a three-necked flask and ultrasonically disperse for 20 minutes, then add ferric acetylacetonate, introduce nitrogen for 10 minutes, heat to 200°C with stirring and continue stirring for 35 minutes, continue to heat to 280°C and continue stirring for 35 minutes, cool to room temperature, wash with n-hexane and anhydrous ethanol for 6 times respectively, and dry to obtain the loaded Fe 3 O 4 The biochar is made of coconut shell biochar, and the particle size of the biochar is 5 nm.
[0041] Step S5: Load Fe 3 O 4 The biochar was added to the mixed acid solution, stirred and reacted at 45°C for 4 hours, filtered, washed with deionized water, and vacuum dried at 80°C for 4 hours to obtain a surface carboxylation biochar product; the surface carboxylation biochar product, hydroxyl product, anhydrous ethanol, and N, N'-dicyclohexyl diimide were added to the reaction bottle under stirring, the temperature was raised to 115°C, and the reaction was stirred at constant temperature reflux for 48 hours, and then centrifuged through isopropanol, and the lower precipitate was vacuum dried at 80°C for 24 hours to obtain a biochar-based organic pollutant adsorption material; Fe loaded 3 O 4 The dosage ratio of biochar and mixed acid solution is 10g:32mL, the mixed acid solution is prepared by mixing concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 3:1, and the mass fractions of concentrated sulfuric acid and concentrated nitric acid are both 98%; the dosage ratio of surface carboxylation biochar product, hydroxyl product, anhydrous ethanol, and N,N'-dicyclohexyldiimide is 13g:28g:220mL:33g.
[0042] Example 3
[0043] A biochar-based organic pollutant adsorption material, the preparation of which comprises the following steps:
[0044] Step S1: placing N,N-dimethyl-7-aminoheptanoic acid and ethanol in a flask, stirring, then adding chloropentadecane, heating to 40°C, stirring at a constant temperature for 12 hours, revolving and recrystallizing with acetone, filtering, and obtaining a quaternary ammonium salt product; adding the quaternary ammonium salt product into distilled water, stirring for 10 minutes, adding porous zeolite, and then oscillating in a water bath at a temperature of 70°C and a speed of 200r / min for 51 hours, washing with water and drying, and obtaining a modified zeolite; the amount ratio of N,N-dimethyl-7-aminoheptanoic acid, ethanol, and chloropentadecane is 0.1mol:95mL:0.1mol, and the volume fraction of ethanol is 95%; the amount ratio of the quaternary ammonium salt product, distilled water, and porous zeolite is 0.1mol:1000mL:400g, and the size of the porous zeolite is 200 mesh;
[0045] Step S2: Add nano titanium dioxide into deionized water, ultrasonically disperse for 40 minutes, then add sodium hexametaphosphate, adjust the pH to 9, heat to 80°C under vigorous stirring, adjust the pH to 10.0, slowly add hydrated silicon dioxide, continue stirring for 1 hour, slowly adjust the pH to 7.0, continue stirring for 30 minutes, filter, wash with water, and dry to obtain surface-coated nano SiO 2 Nano-TiO 2 ; Then the surface is coated with nano-SiO 2 Nano-TiO 2 Add to anhydrous ethanol, ultrasonically disperse for 15 minutes, add 5-hexenyltrimethoxysilane and sulfuric acid solution, stir for 40 minutes, and obtain a coated product with double bonds on the surface; the dosage ratio of nano titanium dioxide, deionized water, sodium hexametaphosphate, and hydrated silicon dioxide is 10g: 60mL: 6g: 0.1g; the surface coated nano SiO 2 Nano-TiO 2 , anhydrous ethanol, 5-hexenyltrimethoxysilane and sulfuric acid solution in a ratio of 8 g: 80 mL: 45 g: 10 mL, and the concentration of the sulfuric acid solution is 0.1 mol / L;
[0046] Step S3: adding the coated product containing double bonds on the surface to dichloromethane, stirring, and then adding 3-chloroperoxybenzoic acid, stirring and reacting at room temperature for 5 hours to obtain an epoxy product; in a nitrogen atmosphere, adding the modified zeolite and toluene to a flask, heating to 45°C, adding pyridine, stirring, adding the epoxy product to the flask, stirring and reacting for 10 hours, and then heating to 120°C, stirring for 2 hours to obtain a hydroxyl product; the amount ratio of the coated product containing double bonds on the surface, dichloromethane and 3-chloroperoxybenzoic acid is 15g:110mL:40g; the amount ratio of the modified zeolite, toluene, pyridine and epoxy product is 35g:150mL:6mol:23g;
[0047] Step S4: Add biochar and oleylamine to a three-necked flask and ultrasonically disperse for 20 minutes, then add ferric acetylacetonate, introduce nitrogen for 10 minutes, heat to 200°C with stirring and continue stirring for 40 minutes, continue to heat to 280°C and continue stirring for 40 minutes, cool to room temperature, wash with n-hexane and anhydrous ethanol for 6 times respectively, and dry to obtain the loaded Fe 3 O 4 The amount ratio of biochar, oleylamine and ferric acetylacetonate is 1.0 g: 60 mL: 2.0 g, the biochar is rice straw biochar, and the particle size of the biochar is 6 nm;
[0048] Step S5: Load Fe 3 O 4The biochar was added to the mixed acid solution, stirred at 50°C for 3-5h, filtered, washed with deionized water, and vacuum dried at 80°C for 4h to obtain a surface carboxylated biochar product; the surface carboxylated biochar product, hydroxyl product, anhydrous ethanol, and N, N'-dicyclohexyl diimide were added to the reaction bottle under stirring, the temperature was raised to 120°C, and the reaction was stirred at constant temperature reflux for 48h, and then centrifuged through isopropanol, and the lower precipitate was vacuum dried at 80°C for 24h to obtain a biochar-based organic pollutant adsorption material; Fe loaded 3 O 4 The dosage ratio of biochar and mixed acid solution is 10g:35mL, the mixed acid solution is prepared by mixing concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 3:1, and the mass fractions of concentrated sulfuric acid and concentrated nitric acid are both 98%; the dosage ratio of surface carboxylation biochar product, hydroxyl product, anhydrous ethanol, and N,N'-dicyclohexyldiimide is 14g:30g:250mL:35g.
[0049] Comparative Example 1
[0050] This comparative example is a commercially available biochar adsorption material.
[0051] Comparative Example 2
[0052] Compared with Example 3, N,N-dimethyl-7-aminoheptanoic acid and chloropentadecane are replaced with N,N-dimethylglycine and 1-chloropropane, respectively, and the rest is exactly the same as Example 3, that is, no long alkane chain is introduced, to obtain a biochar-based organic pollutant adsorption material.
[0053] Comparative Example 3
[0054] Compared with Example 3, the modified zeolite obtained by the reaction in step S3 is replaced by the surface carboxylated biochar product in step S5, that is, the surface is coated with nano-SiO 2 Nano-TiO 2 Fe 3 O 4 The biochar is added without introducing modified zeolite, and then the biochar-based adsorption material is prepared according to step S3.
[0055] The biochar-based organic pollutant adsorption material prepared by the present invention is further tested for its effectiveness, and the test results are as follows.
[0056] Under the conditions of pH 7 and temperature of 25°C, a phenanthrene solution and a benzo(a)pyrene solution with an initial concentration of 50 mg / L were added to a reagent bottle, and then the organic pollutant adsorbent materials obtained in Examples 1-3 and Comparative Examples 1-3 were added to the phenanthrene solution and the benzo(a)pyrene solution at a ratio of 1 g:1 L. After being placed at 25°C for 7 days, the concentrations of the phenanthrene solution and the benzo(a)pyrene solution were measured, and the degradation amounts of phenanthrene and benzo(a)pyrene were calculated. The results are recorded in Table 1.
[0057] Table 1: Test results
[0058]
[0059]
[0060] According to the data in Table 1, it can be seen from the comparison between Examples 1-3 and Comparative Example 1 that, compared with the common biochar adsorption materials available on the market, the biochar-based organic pollutant adsorption material of the present invention has a better adsorption rate for polycyclic aromatic hydrocarbons, and the degradation amount of polycyclic aromatic hydrocarbons is higher. It can be seen from the comparison between Example 3 and Comparative Example 2 that the introduction of long alkane chains into the modified zeolite is more conducive to the adsorption of polycyclic aromatic hydrocarbon organic pollutants by the adsorption material. It can be seen from the comparison between Example 3 and Comparative Example 3 that the use of modified zeolite as a carrier is more conducive to the adsorption of polycyclic aromatic hydrocarbon organic pollutants by the adsorption material. 3 O 4 Biochar and surface-coated nano-SiO 2 Nano-TiO 2 The grafted adsorption material can significantly increase the degradation amount of polycyclic aromatic hydrocarbons and can more effectively adsorb polycyclic aromatic hydrocarbons.
[0061] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.
Claims
1. A biochar-based organic pollutant adsorption material, characterized in that: The adsorption material is prepared by the following steps: Step S1: placing N,N-dimethyl-7-aminoheptanoic acid and ethanol in a flask, stirring, then adding pentadecane chloride, heating to 30-40° C., stirring at constant temperature for 10-12 hours, revolving and recrystallizing with acetone, filtering, and obtaining a quaternary ammonium salt product; adding the quaternary ammonium salt product into distilled water, stirring for 10 minutes, adding porous zeolite, and then oscillating in a water bath at a temperature of 60-70° C. and a rotation speed of 200 r / min for 48-51 hours, washing with water and drying, and obtaining a modified zeolite; Step S2: adding nano titanium dioxide into deionized water, ultrasonically dispersing for 30-40 minutes, then adding sodium hexametaphosphate, and then adjusting the pH to 8-9, heating to 80°C under vigorous stirring, adjusting the pH to 10.0, slowly adding hydrated silicon dioxide, continuing stirring for 1 hour, slowly adjusting the pH to 7.0, continuing stirring for 30 minutes, filtering, washing with water, and drying to obtain nano TiO2 with surface coated with nano SiO2; then adding the nano TiO2 with surface coated with nano SiO2 into anhydrous ethanol, ultrasonically dispersing for 15 minutes, adding 5-hexenyltrimethoxysilane and sulfuric acid solution, stirring for 30-40 minutes, and obtaining a coated product containing double bonds on the surface; Step S3: adding the coated product containing double bonds on the surface into dichloromethane, starting stirring, and then adding 3-chloroperbenzoic acid, stirring and reacting at room temperature for 4-5 hours to obtain an epoxy product; In a nitrogen atmosphere, add modified zeolite and toluene into a flask, heat to 45°C, add pyridine, start stirring, add the epoxy product into the flask, stir and react for 8-10h, then heat to 110-120°C, stir for 1-2h to obtain the hydroxyl product; Step S4: add biochar and oleylamine to a three-necked flask and ultrasonically disperse for 20 minutes, then add ferric acetylacetonate, introduce nitrogen for 10 minutes, heat to 200°C with stirring and continue stirring for 30-40 minutes, continue to heat to 280°C and continue stirring for 30-40 minutes, cool to room temperature, wash with n-hexane and anhydrous ethanol for 6 times respectively, and dry to obtain Fe3O4-loaded biochar; Step S5: adding the Fe3O4-loaded biochar to the mixed acid solution, stirring and reacting at 40-50°C for 3-5h, filtering, washing with deionized water, and vacuum drying at 80°C for 4h to obtain a surface carboxylation biochar product; adding the surface carboxylation biochar product, hydroxyl product, anhydrous ethanol, and N,N'-dicyclohexyl diimide to a reaction bottle under stirring, heating to 110-120°C, stirring and reacting at constant temperature reflux for 48h, and then centrifuging through isopropanol, and vacuum drying the lower precipitate at 80°C for 24h to obtain a biochar-based organic pollutant adsorption material; In step S5, the dosage ratio of Fe3O4-loaded biochar and mixed acid solution is 10g:30-35mL, the mixed acid solution is prepared by mixing concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 3:1, and the mass fractions of concentrated sulfuric acid and concentrated nitric acid are both 98%; the dosage ratio of surface carboxylation biochar product, hydroxyl product, anhydrous ethanol, and N,N'-dicyclohexyldiimide is 12-14g:25-30g:200-250mL:30-35g.
2. The biochar-based organic pollutant adsorption material according to claim 1, characterized in that: In step S1, the dosage ratio of N,N-dimethyl-7-aminoheptanoic acid, ethanol, and chloropentadecane is 0.1 mol: 85-95 mL: 0.1 mol, and the volume fraction of ethanol is 95%; the dosage ratio of the quaternary ammonium salt product, distilled water, and porous zeolite is 0.05-0.1 mol: 1000 mL: 300-400 g, and the size of the porous zeolite is 200 mesh.
3. The biochar-based organic pollutant adsorption material according to claim 1, characterized in that: In step S2, the dosage ratio of nano titanium dioxide, deionized water, sodium hexametaphosphate, and hydrated silicon dioxide is 5-10g: 50-60mL: 3-6g: 0.05-0.1g; the dosage ratio of nano TiO2 with surface coated nano SiO2, anhydrous ethanol, 5-hexenyltrimethoxysilane and sulfuric acid solution is 6-8g: 70-80mL: 42-45g: 8-10mL, and the concentration of the sulfuric acid solution is 0.1mol / L.
4. The biochar-based organic pollutant adsorption material according to claim 1, characterized in that: In step S3, the usage ratio of the coated product containing double bonds on the surface, dichloromethane and 3-chloroperbenzoic acid is 13-15 g: 100-110 mL: 36-40 g; the usage ratio of the modified zeolite, toluene, pyridine and epoxy product is 32-35 g: 140-150 mL: 5-6 mol: 21-23 g.
5. The biochar-based organic pollutant adsorption material according to claim 1, characterized in that: In step S4, the usage ratio of biochar, oleylamine and ferric acetylacetonate is 1.0 g:60 mL:2.0 g, the biochar is one of rice straw biochar, coconut shell biochar and sawdust biochar, and the particle size of the biochar is 4-6 nm.
Citation Information
Patent Citations
Zeolite and polyamino acid compounded medical material with hemostasis function and production method and application thereof
CN111110910A
Microbial preparation and application thereof in polycyclic aromatic hydrocarbon degradation
CN116987601A